Methods for simplifying mathematical models of dynamical systems (MCIT: Proceedings of International scientific and practical conference, 2023)
We consider the problem of simplifying a system of ordinary differential equations obtained as a result of reconstruction from a single observed variable. To solve the problem, we propose two methods: analytical and numerical-analytical. Both methods were applied to a third-order system of ordinary differential equations with polynomial right-hand sides and the results of the methods were compared.Розглянута задача спрощення системи звичайних диференціальних рівнянь, отриманої як результат реконструкції за однєю спостережуваною змінною. Для розв’язання задачі запропоновано два методи – аналітичний та чисельно-аналітичний. Обидва методи були застосовані до системи звичайних диференціальних рівнянь третього порядку з поліноміальними правими частинами і було виконано порівняння результатів методів.
Keywords: dynamical system; time series; model simplification; analytical method; numerical-analytical method